Steering a New Course for Stem Cell Research: NIH's Intramural Center for Regenerative Medicine - Rao, Mahendra S. (AlphaMed Press, 2012)
SUMMARY: The phenomenal progress made in stem cell biology in the past few years has infused the field of regenerative medicine with a great deal of scientific enthusiasm. However, along with the excitement of discovery comes a new sense of translational urgency. The prospect of using embryonic and induced pluripotent stem cell tools and technologies to produce cell-based therapies and other treatments is no longer a distant dream; it is a very real opportunity that demands our attention today. As with most new fields, regenerative medicine has experienced some significant growing pains, and we have identified a number of key obstacles to progress. Given our role as the lead U.S. biomedical research agency and the world's largest supporter of medical research, the National Institutes of Health (NIH) has a responsibility to find ways to reduce or remove many of these obstacles and, consequently, has—and continues—to respond to these challenges in a variety of ways. In this brief essay, we will review our progress and highlight a new development: the founding of a Center for Regenerative Medicine on the NIH campus.